PEMETAAN REFERENSI JURNAL TERKREDITASI NASIONAL : STUDI KASUS ANNALES BOGORIENSES TAHUAN 2012-2017 - Ahmad Saefudin S.; Tupan Tupan (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2019)
Annales Bogorienses is a Nationally accredited scientific journal in the field of biotechnology. This study carried out a reference analysiss of published artichels, from 2012 to 2017 (6 years). The purpose of this reference analysis study was to find out reference distributions based on number, type of reference, type of publication, language, up-to-date sources use, authorship pattern and citation, distribution. From the result of the reference analysis, it shows that there are 1853 references in a span of 6 years or an average of 29.88 references per article. The typeof reference sources used the most is articles with a precentage of 86,19%, and the smallest is proceedings. The biggest type of reference publishing is the printed references with  precentage 87.15%, greater than the online references which has recentage 12.85%. In terms of references language, English references were mostly used with a precentage of 95.20%. In terms of citation, it is known that 99.4% of the references used were outside of Annales Bogorienses journal articles with a ratio of 1: 209.55 compared to the number ofcitations. In terms of the up-to-date sources use, 62% of 10 year-old references were used. This is more than 5 year-old reference use which has a precentage of 89%, than that of single author which have a precentage of 11%. The average number of citation in scientific articles in Annales Bogorienses journal from 2012 to 2017 is 384.2 citation per year.